Manipulation of New Fluorescent Magnetic Nanoparticles with an Electromagnetic Needle, Allowed Determining the Viscosity of the Cytoplasm of M-HeLa Cells - Iliza Ramazanova; Maxim Suslov; Guzel Sibgatullina; Konstantin Petrov; Svetlana Fedorenko; Asiya Mustafina; Dmitry Samigullin (MDPI AG, 2023)
Magnetic nanoparticles (MNPs) have recently begun to be actively used in biomedicine applications, for example, for targeted drug delivery, in tissue engineering, and in magnetic resonance imaging. The study of the magnetic field effect on MNPs internalized into living cells is of particular importance since it allows a non-invasive influence on cellular activity. There is data stating the possibility to manipulate and control individual MNPs utilizing the local magnetic field gradient created by electromagnetic needles (EN). The present work aimed to demonstrate the methodological and technical approach for manipulating the local magnetic field gradient, generated by EN, novel luminescent MNPs internalized in HeLa cancer cells. The controlling of the magnetic field intensity and estimation of the attractive force of EN was demonstrated. Both designs of EN and their main characteristics are also described. Depending on the distance and applied voltage, the attractive force ENs ranged from 0.056 ± 0.002 to 37.85 ± 3.40 pN. As a practical application of the presented, the evaluation of viscous properties of the HeLa cell's cytoplasm, based on the measurement of the movement rate of MNPs inside cells under impact of a known magnetic force, was carried out; the viscosity was 1.45 ± 0.04 Pa·s.